The applicability of hepatocellular carcinoma risk prediction scores in a North American patient population with chronic hepatitis B infection. Issue 8 (30th April 2015) - Abu-Amara, Mahmoud; Cerocchi, Orlando; Malhi, Gurtej; Sharma, Suraj; Yim, Colina; Shah, Hemant; Wong, David K; Janssen, Harry L A; Feld, Jordan J
Abstract : Background: Patients with chronic hepatitis B (CHB) infection are at an increased risk of developing hepatocellular carcinoma (HCC). Risk scores have been developed in Asian populations to predict HCC risk over time. Aim: To assess the performance of HCC risk prediction models in a heterogeneous population of patients with CHB. Methods: Scores were calculated at baseline using CU-HCC, REACH-B, NGM1-HCC, NGM2-HCC and GAG-HCC models and the incidence of HCC was determined. The predictive ability of each score was evaluated using the area under the receiver operating characteristic curve (AUROC), Cox regression and plots of observed versus predicted HCC. The predictive value of the scores was compared between Asian and non-Asian patients and between cirrhotic versus non-cirrhotic with and without treatment. Results: Of 2105 patients, 70 developed HCC. Increasing risk score was associated with HCC in all models. The CU-HCC model had the highest AUROC in Asian (0.85) and non-Asian (0.91) patients. Patients identified as low risk by any model had a very low incidence of HCC (0–0.15 per year), with the highest proportion of patients identified as low risk using CU-HCC (67%) or GAG-HCC (78%). The risk of HCC was similar to predicted for low-risk and medium-risk patients but was lower than predicted for high-risk patients. Treated patients had a lower than predicted risk of HCC, particularly in non-cirrhotic high-risk patients with longer follow-up. Conclusions: Although all models predicted the risk of HCC, models that incorporated parameters of liver function or cirrhosis (CU-HCC/GAG-HCC) were most accurate. Low-risk patients likely require reduced HCC surveillance.